HUBUNGAN SELF CARE DENGAN KOMPLIKASI DIABETES MELLITUS PADA PASIEN DIABETES MELLITUS TIPE II DI POLI PENYAKIT DALAM RSUD DOKTER MOHAMAD SALEH KOTA PROBOLINGGO - Hartono, Dodik (STIKes Maharani Malang, 2019)
Introduction: Self care is self-care that is done to maintain health in bio-psycho-social-spiritual. Things to do to prevent complications of diabetes mellitus, namely to control blood sugar, take medication regularly, exercise and diet accordingly. The purpose of this study was to determine the relationship between self care and the complications of diabetes mellitus in patients with type 2 diabetes mellitus in the internal medicine poly at Dokter Mohamad Saleh Hospital in Probolinggo City. Metho: The type of research used is correlational analytic research with a cross sectional approach. The sample in this study were type 2 DM patients who visited the internal medicine poly at Mohamad Saleh Hospital on Desember 2018 to Januari 2019 and fulfilled the inclusion criteria as many as 57 respondents whose method of extraction was done by purposive sampling technique. Data collection includes coding, editing and tabulating, then the data were analyzed using SPSS 16.0 and obtained spearmank with significant value p value 0.05. Results and Analysis: The results of the study showed that of the 57 respondents most of them had good self care, namely as many as 23 respondents (40.3%) and most had no complications, namely as many as 30 respondents (52.6%). The results of the calculation of the spearman statistical test at a significant level of 5 = 0.05 obtained the value of ? of 0,000 which means that there is a relationship between self care and complications of diabetes mellitus in patients with type 2 diabetes mellitus in Dokter Mohamad Saleh Hospital In Probolinggo City. Discussion: By doing good self-care in daily life it will prevent complications in type 2 diabetes mellitus patients, thus preventing complications in type 2 diabetes mellitus patients. Health workers need to provide information and motivation to patients and families to always provide support in apply self care in everyday life.